Photo‐inactivation of bacteria in hospital effluent via thiolated iron‐doped nanoceria - Sara Khan; Sulaiman Faisal; Dilawar Farhan Shams; Maryam Zia; Akhtar Nadhman (IET Nanobiotechnology)
Hospital wastewater is a major contributor of disease‐causing microbes and the emergence of antibiotic resistant bacteria. In this study, thiolated iron‐doped nanoceria was synthesised and tested for killing of microbes from hospital effluent. These particles were designed to inhibit the efflux pumps of the bacteria found in hospital effluent with further ability to activate in visible light via iron doping thus generating tunable amount of reactive oxygen species (ROS). The quantum yield of the ROS generated by the nanoceria was 0.67 while the ROS types produced were singlet oxygen (36%), hydroxyl radical (31%) and hydroxyl ions (32%), respectively. The particles were initially synthesised through green route using Foeniculum vulgare seeds extract and were annealed at 200°C and further coated with thiolated chitosan to enhance the solubility and efflux pump inhibition. X‐ray diffraction confirmed the polycrystalline nature of nanoparticles and uniform spherical shape with 30 nm size, confirmed by scanning electron microscope. The nanoparticles exhibited 100% bactericidal activity at 100 µg/mL against all the isolated bacteria. The enhanced bactericidal effect of iron‐doped nanoceria could be attributed to efflux inhibition via thiolated chitosan as well as the production of ROS upon illumination in visible light, causing oxidative stress against microbes found in hospital effluent.